1988
DOI: 10.1152/physrev.1988.68.2.608
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and electrophysiology of the mammalian atrioventricular node

Abstract: The AV node of those mammalian species in which it has been thoroughly investigated (rabbit, ferret, and humans) consists of various cell types: transitional cells, midnodal (or typical nodal cells), lower nodal cells, and cells of the AV bundle. There are at least two inputs to the AV node, a posterior one via the crista terminalis and an anterior one via the interatrial septum, where atrial fibers gradually merge with transitional cells. The role of a possible third input from the left atrium has not been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
146
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(154 citation statements)
references
References 100 publications
4
146
0
Order By: Relevance
“…Later, combined histological and electrophysiological studies described a zone of transitional cells bordering the compact AV node. 8,9 In the present study, direct recording of AV nodal electrograms and correlation with histology show that AV nodal reentry occurs in this complex network of nodal and transitional cells and in the rim of surrounding atrial cells. McGuire et al 23 found that atrial cells contiguous with the AV node reveal nodal-type electrophysiology.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Later, combined histological and electrophysiological studies described a zone of transitional cells bordering the compact AV node. 8,9 In the present study, direct recording of AV nodal electrograms and correlation with histology show that AV nodal reentry occurs in this complex network of nodal and transitional cells and in the rim of surrounding atrial cells. McGuire et al 23 found that atrial cells contiguous with the AV node reveal nodal-type electrophysiology.…”
Section: Discussionsupporting
confidence: 56%
“…However, morphological, electrophysiological, and clinical observations suggest that the AV node includes both of the cell groups that determine its functional properties, namely, transitional and compact nodal cells. 8,9 We recently showed that in canine hearts, reentry during ventricular echoes is confined to the AV node. 10 The underlying mechanisms of unidirectional conduction block and slow conduction are also controversial.…”
mentioning
confidence: 99%
“…An experimental study has demonstrated that AV nodal conduction is determined by discrete anteroseptal and posteroseptal atrionodal inputs that are associated with differential functional properties. 24 Clinically, Markowitz et al 25 suggested that successful slow pathway ablation is achieved by selective ablation of the posterior atrionodal input.…”
Section: Tachycardia Circuit In Avnrtmentioning
confidence: 99%
“…12,13) However, it has been reported that multiple AV nodal pathways exist in some patients, and that some of them are located in the deeper layers of the atrial septum, and are connected to perinodal atrial tissues. [5][6][7] In some cases with such connection, especially to the left atrium, it is likely that atypical AVNRT is induced by eccentric retrograde left-sided activation. 8,10,14) In the present electrophysiologic study, double observations of the jump-up phenomenon suggest that triple AV nodal pathways are present.…”
Section: Discussionmentioning
confidence: 99%
“…4) It has recently been reported that multiple AV nodal pathways exist in patients with the atypical type of AVNRT, and that some of the pathways are located in the deeper layers connected to perinodal atrial tissues. [5][6][7] Hwang, et al have reported that AVNRT with left-sided activation, which may occur with such a connection, is relatively rare. 8) In this report, we describe a patient with AVNRT caused by a left-sided pathway that was confirmed by the success of radiofrequency catheter ablation.…”
mentioning
confidence: 99%